Synthesis Of L-Menthyl Acetic by Esterification L-Menthol and Acetic Anhydride with Variation Of Time - Novia Suryani; A Ghanaim Fasya; Rurini Retnowati; Akyunul Jannah (Al-Kimia, 2020)
l-menthyl acetic is an ester with specific aroma that synthesized by reaction of l-menthol and acetic anhydride and useful in fragrance industry. This paper reports influenced variation of time reaction toward ester product and characteristics l- menthyl acetic based on TLC, FTIR, GC and GC-MS. Reaction using l-menthol, acetic anhydride and catalyst H2SO4 98 % in diethyl eter solvent at temperature 60 °C with variation of time reaction (45, 60, 75, 90, 105 minutes). The result of research is variation of time influence product with highest yield 88,43 % for 90 minutes. Monitoring TLC achived Rf = 0,82; analysis by FTIR achived specific wave number ester 1736,96 cm-1; analysis by GC achived tr = 14,82 minutes and analysis by GC-MS achived tr = 16,13 minutes with base peak m/z = 95.